(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
Derivative nouns are considered in the article, which are formed by a suffixes method and used in modern prose work. The most productive suffix formants are set and the features of semantics of analysid derivates are certained.